2004
DOI: 10.1111/j.0022-3506.2004.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Personal Growth in Adults' Stories of Life Transitions

Abstract: This study identified four themes of personal growth (integrative, intrinsic, agentic, and communal) in adults' stories of life transitions in careers and religions. Specific themes were expected to relate differentially to two forms of personality development (socialcognitive maturity and social-emotional well-being) and to transition satisfaction. Integrative themes correlated primarily with social-cognitive maturity (ego development; Loevinger, 1976), whereas intrinsic themes correlated primarily with socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
239
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(271 citation statements)
references
References 63 publications
26
239
0
6
Order By: Relevance
“…All the variables show significant positive relationships. Similar findings were reported in previous studies for PGI and life satisfaction (Bauer & McAdams, 2004;Brink, 2012;Hardin, Weigold, & Robitschek, 2007;Sood, Gupta, & Bakhshi, 2012;Stevic & Ward, 2008); for PGI and happiness (Hardin, Weigold, & Robitschek, 2007;Neff, Rude, & Kirkpatrick, 2007); for happiness and life satisfaction (Barrett, 1980, Unpublished Master's Dissertation;Poursardar, Sangari, Abbaspour, & Alboukurdi, 2012) in a study demonstrated effect of happiness on life satisfaction.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…All the variables show significant positive relationships. Similar findings were reported in previous studies for PGI and life satisfaction (Bauer & McAdams, 2004;Brink, 2012;Hardin, Weigold, & Robitschek, 2007;Sood, Gupta, & Bakhshi, 2012;Stevic & Ward, 2008); for PGI and happiness (Hardin, Weigold, & Robitschek, 2007;Neff, Rude, & Kirkpatrick, 2007); for happiness and life satisfaction (Barrett, 1980, Unpublished Master's Dissertation;Poursardar, Sangari, Abbaspour, & Alboukurdi, 2012) in a study demonstrated effect of happiness on life satisfaction.…”
Section: Resultssupporting
confidence: 85%
“…PGI has been associated with both increase in well being and decrease in distress (Robitschek & Kashubeck, 1999); feeling satisfied with life (Hardin, Weigold, & Robitschek, 2007;Sood, Gupta, & Bakhshi, 2012;Stevic & Ward, 2008). People who interpret their life transitions in terms of growth have higher levels of life satisfaction (Bauer & McAdams, 2004;Brink, 2012). Review of literature reflects the linkage between PGI and happiness as well (Hardin, Weigold, & Robitschek, 2007;Neff, Rude, & Kirkpatrick, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…with global measures of psychological well-being and health, none of which showed a direct relationship in adulthood (Bauer & McAdams, 2004a, 2004bHelson & Roberts, 1994;Helson & Wink, 1992;Vaillant, 1977;Vaillant & McCullough, 1987;Westenberg & Block, 1993). In other words, people who can think maturely about their lives seem roughly as likely to be happy as unhappy.…”
Section: Maturity and Well-beingmentioning
confidence: 99%
“…Personality traits, interpersonal styles, and behavioral signatures can then be correlated with these lifespace areas and to the person's life story more generally (Acton & Revelle, 2002;Bauer & McAdams, 2004).…”
Section: The Dynamics and Development Of Personalitymentioning
confidence: 99%